High prevalence of helminths infection and associated risk factors among adults living in a rural setting, central Kenya: a cross-sectional study - Janet Masaku (Tropical Medicine and Health, 2017)
Abstract Background Schistosome infection and soil-transmitted helminths (STHs) are major public health problems in many developing countries where they contribute to the suffering of populations living in poor settings. A cross-sectional survey was conducted in four rural villages in central region of Kenya to provide information on the status of schistosome and STH infections. Previous studies conducted in the area among primary school children showed that there were high STH and Schistosoma mansoni infections. This paper presents the results of a parasitological investigation and the associated risk factors of infection among adults living in the study villages. Methods A total of 495 adults (18–84 years) from systematically selected households were sampled during this cross-sectional survey. They were interviewed and screened for S. mansoni and STHs using duplicate Kato-Katz thick smears. Comparison of prevalence by age group and gender was explored by confidence interval plots, and 95% CI were obtained by generalized least squares (GLS) random effects model. Risk factors associated with S. mansoni infection were determined using mixed effects logistic regression at 95% CI taking into account household clusters. Results The study revealed that the prevalence of S. mansoni infection was 33.5% (95% CI 29.6–38.0) among adults in the study villages, while the prevalence of STH infection was 0.2% (95% CI 0–1.4) with hookworm being the only detected STH species. However, the village and education level were the only risk factors which showed significant evidence of association with S. mansoni infections. Conclusions The current study shows that adult communities in the study area were highly infected with S. mansoni. The study suggests that it may be necessary to develop contemporary approaches towards preventive chemotherapy interventions to adults in high endemic areas to complement the ongoing school-based deworming programme.